2015
DOI: 10.1108/er-03-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Getting a low-paid job in French and UK supermarkets: from walk-in to online application?

Abstract: Purpose – The purpose of this paper is to compare the recruitment practices of the French and UK retail industry. It analyses the influence of specific business constraints, labour market institutions and employment patterns on recruitment practices. It devotes attention to incidences of the shift from classic to web-based hiring methods. Design/methodology/approach – The cases of two leading food retail chains are explored. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…That is why, even if new criteria are not explicitly adopted, changing recruitment practices is likely to have an impact on the profiles of those hired. In food retail in France and in the UK, Rieucau (2015) studies the implementation of formal recruitment procedures that remove traditional face-to-face interactions (applications are hand-delivered by job seekers directly at superstores) by at-a-distance interactions (online applications are centralised by HR professionals at headquarters). She shows that by prioritising computer literacy and signals written in online applications, the at-a-distance recruitment procedure favours students and younger workforce at the expense of long-term unemployed and older individuals.…”
Section: The Impact Of Hiring Methods On the Profiles Of Employees Hiredmentioning
confidence: 99%
“…That is why, even if new criteria are not explicitly adopted, changing recruitment practices is likely to have an impact on the profiles of those hired. In food retail in France and in the UK, Rieucau (2015) studies the implementation of formal recruitment procedures that remove traditional face-to-face interactions (applications are hand-delivered by job seekers directly at superstores) by at-a-distance interactions (online applications are centralised by HR professionals at headquarters). She shows that by prioritising computer literacy and signals written in online applications, the at-a-distance recruitment procedure favours students and younger workforce at the expense of long-term unemployed and older individuals.…”
Section: The Impact Of Hiring Methods On the Profiles Of Employees Hiredmentioning
confidence: 99%
“…Nor do they consider the ways in which automated processes outside the control of job seekers can influence the outcomes of a job search (O'Neil 2016). Rieucau (2015) demonstrates in her investigation of online job recruitment experiences among French and British entry level workers that e-recruitment (which she calls 'at-adistance' hiring channels) places a premium on literacy skills, technology know-how and digital access, creating a situation in which often the digital literacy skills required to apply for jobs exceeds the literacy demands of the job itself. In her study of how migrant workers and their volunteer tutors in the UK navigate online job applications, De Pauw (2020) similarly demonstrates the complex and sophisticated nature of online job platforms and observes the tension between these complexities and the relative dearth of adult education programs to support job seekers in this process, even though the United Kingdom has adopted a 'digital by default' policy through which adults must access services and resources online, and must demonstrate that they are actively seeking jobs on online platforms.…”
Section: Framing Literaturementioning
confidence: 99%
“…Some employers also deploy algorithmic sorting of top placements according to personality tests/questions and screening (Pfieffelmann et al 2010). Rieucau (2015) found that recruitment strategies that involve at-a-distance recruitment are also becoming more common in low-wage sector employment such as construction, retail and service sectors, particularly when these sectors are overtaken by large companies (such as McDonalds, Amazon, Walmart and so on) that have the capacity to design and manage their own recruitment portals. However, smaller and professional sector employers are also turning to automation, with actual resource managers reviewing r esum es selected among the results of automated screenings and personality tests (see for example Elizabeth 2019).…”
Section: Automation and E-recruitmentmentioning
confidence: 99%
See 2 more Smart Citations